Employer brand scale development and validation: a second-order factor approach. Issue 2 (6th March 2017) - Tanwar, Karnica; Prasad, Asha
Abstract : Purpose: The purpose of this paper is to conceptualise, develop and validate a scale to measure the employer brand from the perspective of existing employees. Design/methodology/approach: The methodology entailed the compilation of a literature review and conduction of qualitative interviews to generate items. Five employer brand dimensions have been derived through exploratory factor analysis and further validated through confirmatory factor analysis by using a separate data of 313 employees. Also, the employer brand has been specified as a second-order factor that is determined by five first-order factors. Findings: A final 23-item EB scale covering five dimensions of the employer brand has been developed. The dimensions identified are: a healthy work atmosphere, training and development, work-life balance, ethics and corporate social responsibility, and compensation and benefits. Also, the higher order measurement model suggests that employer brand is most influenced by the "healthy work atmosphere" dimension. These dimensions reflect the perceptions of existing employees regarding their organisation. The scale is found to be psychometrically sound for measuring the employer brand. Practical implications: The scale is useful for both researchers and practitioners. A deeper insight into the dimensions may help managers to identify their impact on organisational outcomes like employee satisfaction, employee retention, commitment and productivity. Also, organisations can measure the perceptions of employees for identifying improvement gaps and developing effective attraction and retention strategies. The scale also provides researchers with a sought-after conceptualisation of employer brand. Originality/value: The authors believe that the study is the first of its kind wherein the employer brand has been modelled as a second-order factor from the perspective of the existing employees.